2019
DOI: 10.1016/j.jsxm.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Self-Reported Sexual Function Among Physically Active Adults

Abstract: Background: Sexual dysfunction is common among adults and takes a toll on quality of life for both men and women. Aim: To determine whether higher levels of weekly cardiovascular exercise are protective against self-reported sexual dysfunction among men and women. Methods: We conducted an international online, cross-sectional survey of physically active men and women between April and December 2016, assessing exercise activity categorized into sextiles of weekly metabolic equivalent-hours. Odds ratios (ORs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
(45 reference statements)
2
16
0
1
Order By: Relevance
“…On the one hand, it is possible that cardiometabolic and psychological benefits of exercise through cycling improve sexual function and possibly reduce sexual pain. 10 , 11 , 12 , 13 On the other hand, vulnerable patients susceptible to genital numbness while cycling are at risk of sexual pain and FSD. Prior studies have identified muscle hypertonus as a risk factor for sexual pain, 22 which may be increased in cyclists and other athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, it is possible that cardiometabolic and psychological benefits of exercise through cycling improve sexual function and possibly reduce sexual pain. 10 , 11 , 12 , 13 On the other hand, vulnerable patients susceptible to genital numbness while cycling are at risk of sexual pain and FSD. Prior studies have identified muscle hypertonus as a risk factor for sexual pain, 22 which may be increased in cyclists and other athletes.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Yet frequency and duration of cycling were notably not associated with FSD, 9 and other studies have identified exercise as a protective factor against FSD of which sexual pain is a sub-component. 10 , 11 , 12 , 13 However, using the composite outcome variable of FSD may mask the effect of exercise on sexual pain, and it remains unknown whether exercise is protective against sexual pain specifically, and if not, what factors influence pain.…”
Section: Introductionmentioning
confidence: 99%
“…Both sexes were examined simultaneously in the present study, but there is little evidence in this regard. Fergus et al (2019) showed the effect of exercise on reducing erectile dysfunction in men and protecting women against sexual dysfunction [ 47 ]. Exercise seems to activate the sympathetic nervous system and endocrine stimulates sexual function in women physiologically [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is also assumed to improve the arterial supply of the penis [ 47 ] and it is well known that the penis and clitoris are common in embryonic origin and both organs have erectile tissue, skeletal muscle, and nervous system [ 48 ]. On the other hand, reflexologists believe that the foot is a reduced map of the whole body and reflects all the organs and parts of the body, and the arrangement of the body parts on the foot corresponds to their orders in the body [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Particularly in patients with these metabolic morbidities, lifestyle adjustments are thought to reduce the burden of ED and its progression by decreasing low-grade clinical inflammation and improving overall body habitus. [7][8][9][10] Through these shared biologic pathways, reduction of oxidative stress, and subclinical inflammation through lifestyle intervention can ameliorate endothelial dysfunction and improve insulin insensitivity. 7,8 In this regard, it is clear that weight loss, regular exercise, and smoking cessation can significantly improve ED.…”
Section: Discussionmentioning
confidence: 99%